Early intraocular lens explantations: 10-year database analysis - Friedrich, Maximilian; Son, Hyeck Soo; Hassel, Oliver; Teich, Lilly; Augustin, Victor A.; Khoramnia, Ramin; Auffarth, Gerd U.; Yildirim, Timur Mert (BMC ophthalmology, 2024)
The aim of this study was to analyze the causes and characteristics of IOL explantation within the first year after primary implantation.
Gesehen am 26.11.2024